Turkish doctors' cohort: healthy despite low screening. Issue 3 (3rd April 2017) - Unal, Serhat; Tanriover, Mine Durusu; Ascioglu, Sibel; Demirkazik, Ahmet; Ertenli, Ihsan; Eskioglu, Erdal; Guler, Kerim; Kiraz, Sedat; Ozbakkaloglu, Mert; Ozer, Birol; Tukek, Tufan; Akyar, Serra; et al.
ABSTRACT: Objectives : We aimed to determine the prevalence of chronic diseases and unhealthy lifestyle behaviors of Turkish doctors as compared with the general population and the frequency of compliance with preventive clinical practices among doctors. Methods : This was an observational, prospective cohort study that enrolled graduates between 1975 and 2004 from six medical schools in Turkey. Data on demographics, disease conditions, and unhealthy lifestyle behaviors were gathered. Preventive care practices were analyzed with regards to age and gender. Results : A total of 7228 doctors participated in the study. Comparison with the national data revealed higher hyperlipidemia and coronary artery disease rates. While 54.5% of the doctors had a doctor visit in the last 12 months, only 31.5% of those over 40 years of age reported a recent blood pressure measurement. Colon cancer screening rate over 50 years of age with any of the acceptable methods was only 3%. One-fourth of the female doctors over 40 years of age underwent mammography within the last two years. Only 7.1% of the doctors over 65 years of age and 10% of the doctors having an indication for a chronic disease had a pneumococcal vaccine, while nearly one-fifth had no hepatitis B vaccine. Conclusion : In this cohort of mainly middle-aged Turkish doctors, the age-standardized rates of chronic diseases were lower than the rates in the general population except for the rates of hyperlipidemia and coronary artery disease. However, doctors did show quite low rates of receipt of screening practices. These results might provoke questions about how to use Turkish doctors' health behaviors to further improve doctors' and, relatedly, patients' health.